Strategi Komunikasi Waria terhadap Stereotype Sosial di Kota Bukittinggi - Fika Fauzia; Syafwan Rozi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The focus of this research is on how transgender communication strategies relate to social stereotypes in the city of Bukittinggi. In life, a person is never separated from the name of communication, this is because communication is an inherent activity in humans who are classified as social beings, humans cannot live without communication anda communicationt itselt is an important element that forms and anables society. In principle, society cannot be separated from social problems because society has developed and changed from time to time, stereotypes are labels given by society to certain groups. This research is motivated by transgender communication strategies in which they always get social stereotypes but they can still be persistent even carrying out their activities, how to conduct interviews and observations on informants related to this phenomenon. This research resulted in an explanation of the social stereptypes of people in the city of Bukittinggi. The first social stereotypes here is divided into two, namely the classification of condition in which this the classification of this condition is someone who has personality traits and irability, namely the behavioral traits that are inherent in a person. Two communication strategies, this is where a transgender will carry out a communication strategies when he gets a stereotype so that he can survive and move on with his life.